Types and Role of Bows in Modern Vietnamese Culture - S. E. Glazunova; E. B. Morozova (Концепт: философия, религия, культура, 2023)
Recent decades have seen a drastic increase of academic interest in non-verbal communication of various ethnic groups. However, gestural behaviour of the Vietnamese, particularly in the sphere of etiquette, has been rarely analyzed by modern scholars. Research papers on this topic describe etiquette gestures of Vietnamese culture, especially bows, vaguely and sketchily. Although in the past bows used to be widespread in Vietnam, nowadays the gesture seems to have lost its popularity, in comparison with Vietnam’s regional neighbours, such as China, South Korea or Japan. During the preliminary stage of the research, we identified many problem areas concerning rules and situations when people must bow, types, names, and physical forms of Vietnamese bows, which defined the purposes of the research. The goals of the paper are to analyze and systemize the descriptions of Vietnamese bows, rules and situations of their use collected in research literature; to analyze current articles on bows, published by Vietnamese media to understand public opinion about bows and to conduct an online-survey of Vietnamese people (71 people) to obtain additional data, which will help to get more accurate and up-to-date information on the subject. The objective of the research is to identify the role and types of bows in modern Vietnamese culture. The results of the paper show that Vietnamese culture has two basic types (forms) of bows — vái and lạy, with many reduced and intermediate forms, and a nod, which do not have any specific names and require further investigation. The research also identifies numerous etiquette situations where bows are still used and describes rules of bowing in three major contexts of social interaction, such as religious, ceremonial and every-day communication. The results of the media articles and survey analyses show that bows, banned by the Vietnamese Communist Party several decades ago, are gradually starting to acquire more significance in modern society than they had in the past, particularly in business sphere and during religious worships. The results of the paper are not final as the research has outlined new vectors and areas of investigation that require field studies in the country.